Pengaruh Penyinaran Qth Dan Led Pada Kekuatan Tekan Resin Komposit Bulkfilldengan Berbagai Ketebalan - Atia Nurul Sidiqa; Badi Soerachman (Jurnal Material Kedokteran Gigi, 2017)
The incremental layering technique with a 2mm maximum depth is a standard procedure to produce a perfect resin composite with a high mechanical strength. Recent studies has developed bulkfill composite resin that can be done to a depth of more than 4mm. Composite resin polymerization process through irradiation can be obtained by the use of Quartz-Tungsten-Halogen (QTH) and Light Emitting Diodes (LED). One of the mechanical properties needed for the restorative material is good compressive strength to withstand a load of chewing time during the process of mastication function. The purpose of this study to determine the effect of irradiation QTH and LED on the compressive strength of composite resin bulkfill with thickness variations of 4 and 6mm. Teflon mold were used to prepare the resin bulkfill spesimen (6mm in diameter x 4mm in length) bulkfill disk 6mm diameter with a thickness of 4mm (n=5) and 6mm (n=5). Samples were soaked in distilled water with a temperature of 37ºC for 24 hours and then do the pressure test measurements by using Universal Testing Machine (UTM) with 250kgf load and speed of 0.5 mm/min. Shapiro-Wilk normality test and unpaired t-test used in this study.The results of the study there is no influence thickness was statistically significant (a=0.05) in the composite resin bulkfill thickness of 4mm and 6mm in LED and QTH irradiation group with a value of compressive strength 4mm group (147.82 ± 24,35MPa) and sample 6mm (133.76±30.63 MPa), QTH light source sample 4mm (158,21 ± 18,61Mpa), 6mm (154,23±21,43Mpa). LED and QTH no significant difference (p>0.05) in a thickness of 4mm and 6mm. Conclusion, bulkfill composite resin can be applied to the LED and QTH to a depth of 6mm without effecting the bulkfill compressive strength.